Analysis of the Influence of Café Atmosphere, Sales Promotion, Service Quality and Merchandise on Interest and Repeat Purchases at Starbucks Café - Rahim, Nadillah Aatifah; Waluyo, Minto (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
The food and beverage industry is experiencing rapid growth, as evidenced by the increasing number of cafes appearing in various locations. The decision of the general public to visit cafes is no longer solely based on the quality of the food and drinks rather, it is influenced by several factors and considerations that contribute to their purchasing interest. These factors include the availability of sales promotions, a pleasant ambiance, high-quality service, and the sale of appealing merchandise products. The purpose of this thesis is to determine the effect of the variables of cafe atmosphere, sales promotion, service quality, merchandise, on interest and repeat purchases at starbucks cafe. The study utilizes the Structural Equation Model (SEM) and the Marketing Mix 7P concept to analyze and describe the data. The result of this research is Cafe atmosphere cannot be proven in this study because the variable cafe atmosphere was removed from the research model. Sales promotion has no positive and significant effect on purchase intention and repeat purchases. Service quality has a positive and significant effect on interest and repeat purchases, merchandise has a positive and significant effect on interest and repeat purchases. Purchase interest has a positive and significant effect on repeat purchases. The simultaneous equation analysis demonstrates the effects of cafe atmosphere, sales promotion, service quality, and merchandise on Starbucks as follows: Y2 = -0.0145X1 + 0.099X3 + 0.262X4 + Z5.